Predictors of Nonsentinel Nodal Involvement to Aid Intraoperative Decision Making in Breast Cancer Patients with Positive Sentinel Lymph Nodes. (16th August 2011) - Tan, Ern Yu; Ho, Bernard; Chen, Juliana J. C.; Ho, Pey Woei; Teo, Christine; Earnest, Arul; Chan, Patrick M. Y.
Abstract : Background . Up to 60% of patients with a positive sentinel lymph node (SLN) have no additional nodal involvement and do not benefit from completion axillary lymph node dissection (ALND). We aim to identify factors predicting for non-SLN involvement and to validate the MSKCC nomogram and Tenon score in our population. Methods . Retrospective review was performed of 110 consecutive patients with positive SLNs who underwent ALND over an 8-year period. Results . Fifty patients (45%) had non-SLN involvement. Non-SLN involvement correlated positively with the number of positive SLNs (P = 0.04 ), macrometastasis (P = 0.01 ), and inversely with the total number of SLNs harvested (P = 0.03 ). The MSKCC nomogram and Tenon score both failed to perform as previously reported. Conclusions . The MSKCC nomogram and Tenon score have limited value in our practice. Instead, we identified three independent predictors, which are more relevant in guiding the intraoperative decision for ALND.